Supertrends : 50 things you need to know about the future - Tvede, Lars (Gildan Audio, 2020)
Supertrends: 50 Things You Need to Know About the Future is about how efficient futurists work, and how we can expect the world to evolve in terms of demographics, general economics, technologies, business models, resources, environment, and lifestyles. This book addresses how to predict the future, what we can expect from it, and how companies and government should adapt to the accelerating change, and will also: - Explain the core principles of efficient forecasting- List a number of underlying drivers and recurring social patterns which help explain and predict events- Show how companies and governments can become more future-proof by adopting new and innovative management principles- Introduce new technologies and how they will be applied.